2019
DOI: 10.21285/2227-2925-2019-9-3-420-429
|View full text |Cite
|
Sign up to set email alerts
|

Study of the influence of Medusomyces gisevii Sa-12 inoculum dosage on bacterial cellulose yield and degree of polymerisation

Abstract: Bacterial cellulose (BC) consists in a highly crystalline nanopolymer whose potential for application in both traditional and new industries is significant due to its unique physico-mechanical properties. In scaled BC biosynthesis processes, the use of microorganism consortia characterised by their adaptability and synergistic effects when coordinating substrate consumption appears to be promising. In the present work, the effect of inoculum dosage on BC yield during Medusomyces gisevii Sa-12 symbiotic culture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 2 publications
0
3
0
2
Order By: Relevance
“…Shi et al [ 48 ] made no assumptions of the nature of the observed phenomenon. In our previous study [ 24 ], we hypothesized that this could be explained physiologically: the cell population condition worsens over time, that is, the nutrients are running low and metabolic products are building up, therefore the DP of the synthesized BC declines as well. The present study has proved our earlier suggested hypothesis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Shi et al [ 48 ] made no assumptions of the nature of the observed phenomenon. In our previous study [ 24 ], we hypothesized that this could be explained physiologically: the cell population condition worsens over time, that is, the nutrients are running low and metabolic products are building up, therefore the DP of the synthesized BC declines as well. The present study has proved our earlier suggested hypothesis.…”
Section: Resultsmentioning
confidence: 99%
“…The static culture method is well studied. The biosynthesis phases of BC have been established to correlate directly with cell growth phases, and the maximum buildup of BC is observed at a maximum cell count [ 16 , 24 ]. Mathematical models of cell growth, substrate/oxygen intake and BC biosynthesis have been designed [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that the degree of polymerization of BC samples depends on the dosage of inoculum and the duration of biosynthesis. Thus, it is possible to control the biosynthesis process and the degree of polymerization [69,216]. Interestingly, the degree of polymerization of plant cellulose isolated of oat husks is in the range of 1000 -1500 [44].…”
Section: Bacterial Nanocellulosementioning
confidence: 99%
“…СП исходной ХвЦ, образцов композиционной бумаги и исходной БНЦ определялась методом, основанным на растворении навески образца в кадоксене и последующей вискозиметрии полученного раствора [25,26]. Полуширина доверительного интервала определена при уровне значимости 0,05 и составляет ±50.…”
Section: экспериментальная частьunclassified
“…(видовой состав культуры детально приведен в работах [27,28]). Культуральная жидкость получена на полусинтетической питательной среде согласно [26] Полученные данные свидетельствуют о преимуществе метода с поверхностным нанесением БНЦ на отливки из ХвЦ и согласуются с результатами исследований, представленными в работах [3,6,9,13], где добавление БНЦ в бумагу позволило увеличить прочностные и деформационные показатели. В литературе описано увеличение прочностных характеристик внесением волокон БНЦ в количестве до 20% в композицонную бумагу, но отсутствуют результаты визуали-зации процесса взаимодействия микро-и наноразмерных волокон целлюлозы.…”
Section: экспериментальная частьunclassified